The School of Rock - Linklater, Richard; Black, Jack.; Adam Pascal; Lucas Papaelias; Chris Stack; Sarah Silverman; Mike White; Lucas Babin; Joan Cusack; JordanClaire Green; Veronica Afflerbach; Miranda Cosgrove; et al. (USA Paramount Pictures, 2003)
Down and out rock star Dewey Finn (Black) gets fired from his band, and he faces a mountain of debts and depression. He takes a job as a 4th grade substitute teacher at an uptight private school where his attitude and hijinx have a powerful effect on his students. He also meets Zack, a 10-year-old guitar prodigy, who could help Dewey win a "battle of the bands" competition, which would solve his financial problems and put him back in the spotlight.
After being fired from his own band, the guitar player Dewey Finn (Jack Black) needs to raise some money to pay for his rent and his bills. When his friend and school teacher Ned Schneebly (Mike White) is called to a temporary work in an expensive private school, Dewey pretends to be Ned and accepts the job. He finds talented young musicians in his class, and he decides to form a rock-and-roll band with the students and win a competition called "Battle of Bands" to raise the prize and be recognized in the show business.
Take Notes.
Languages: English, Turkish, German Subtitles: English, Turkish, German
Keywords: Comedy; Music